2017
DOI: 10.1136/bmjopen-2016-014769
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review of potential quality indicators for hip fracture patient care

Abstract: ObjectiveThe purpose of this study is to identify existing or potential quality of care indicators (ie, current indicators as well as process and outcome measures) in the acute or postacute period, or across the continuum of care for older adults with hip fracture.DesignScoping review.SettingAll care settings.Search strategyEnglish peer-reviewed studies published from January 2000 to January 2016 were included. Literature search strategies were developed, and the search was peer-reviewed. Two reviewers indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 98 publications
(48 reference statements)
1
3
0
1
Order By: Relevance
“…The broad spectrum of the identified QIs is in line with a recent scoping literature review of (potential) QIs for HF care conducted by Pitzul et al [ 72 ]. As opposed to their review in which they grouped the QIs in a limited number of constructs, we evaluated the QIs individually and retrieved the available evidence for the methodological quality of the identified QIs.…”
Section: Discussionsupporting
confidence: 68%
“…The broad spectrum of the identified QIs is in line with a recent scoping literature review of (potential) QIs for HF care conducted by Pitzul et al [ 72 ]. As opposed to their review in which they grouped the QIs in a limited number of constructs, we evaluated the QIs individually and retrieved the available evidence for the methodological quality of the identified QIs.…”
Section: Discussionsupporting
confidence: 68%
“…Para mejorar la atención en emergencia geriátrica en Alemania, se han desarrollado indicadores de calidad basados en instrumentos QUALIFY, se extrapolaron y operativizaron sesenta y siete indicadores (33 Procesos, 29 de estructura y 5 indicadores de resultado), estos con la finalidad de implementar en la práctica diaria, cinco declaraciones de calidad definidas como GeriQ-ED © TOP 5: Detección de delirio, Realizar un historial completo de medicamentos incluyendo la evaluación de las indicaciones, educación de conocimientos geriátricos y habilidades al personal de emergencia, detección de pacientes con necesidades geriátricas, e identificación de pacientes con riesgo de caídas o caídas recurrentes (Schuster et al, 2020). Por otra parte, Instituto Nacional para la Excelencia en Salud y Cuidado (NICE), y la Asociación Británica de Ortopedia (BOA), en el Reino Unido; han desarrollado indicadores de calidad para la atención de fractura de cadera, centrados en la fase aguda (tiempo para la cirugía, evaluación por orto-geriátrico dentro de las 72 horas posteriores a la admisión) (Pitzul et al, 2017). Los indicadores potenciales para la fase post-aguda desarrollado Mientras que la implementación de las unidades de corta estancia (UCE), pueden contribuir a mejorar la gestión de los hospitales, según los indicadores de calidad global y los indicadores de servicio de la atención como: Ingresos, destino final (alta domiciliaria y hospitalización a domicilio), porcentaje de altas (externas, internas, en fin de semana), reingreso, mortalidad (Richard Espiga et al, 2017).…”
Section: Discussionunclassified
“…The absence of a definition for quality indicators results in inconsistencies for how an indicator should be presented and also what makes for a good indicator. Previous reviews have also found variability in quality indicator definitions, such as indicators for hip fracture patient care 34. The absence of a standard definition of PC-QIs poses concerns for standardised measurement of PCC, and for implementation of PC-QIs in healthcare settings.…”
Section: Discussionmentioning
confidence: 99%